1996
DOI: 10.1063/1.116701
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic calculations of ion implantation in Si: Point defect and transient enhanced diffusion phenomena

Abstract: A new atomistic approach to Si device process simulation is presented. It is based on a Monte Carlo diffusion code coupled to a binary collision program. Besides diffusion, the simulation includes recombination of vacancies and interstitials, clustering and re-emission from the clusters, and trapping of interstitials. We discuss the simulation of a typical room-temperature implant at 40 keV, 5×1013 cm−2 Si into (001)Si, followed by a high temperature (815 °C) anneal. The damage evolves into an excess of inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(71 citation statements)
references
References 4 publications
3
68
0
Order By: Relevance
“…The simulation results suggest a reduction of 40% of the BCA-estimated total implantation damage. The postimplantation damage is stored in small defect aggregates [26] corresponding to space-dependent cluster size distributions of I -and V -type aggregates. Note that the I and V distributions are always superimposed due to fast rates of the point-defect-pointdefect or point-defect-cluster interactions with respect to the particle diffusion.…”
Section: A Calibration and Initialization Of Kmc And Pde Modelsmentioning
confidence: 99%
“…The simulation results suggest a reduction of 40% of the BCA-estimated total implantation damage. The postimplantation damage is stored in small defect aggregates [26] corresponding to space-dependent cluster size distributions of I -and V -type aggregates. Note that the I and V distributions are always superimposed due to fast rates of the point-defect-pointdefect or point-defect-cluster interactions with respect to the particle diffusion.…”
Section: A Calibration and Initialization Of Kmc And Pde Modelsmentioning
confidence: 99%
“…Such treatments Will be critical to an eventual filly predictive modeling of the transient enhanced d f i i o n process. [5] higher temperature annealing these clusters provide a source of point defects for subsequent interstitial or vacancy enhanced migration of the implanted dopant atoms. [6] A schematic illustration of the process is given in Fig.…”
Section: And -mentioning
confidence: 99%
“…Processes like diffusion of defects under high temperature anneal, as in semiconductor doping, or amorphization processes, that depend on the ion flux can not be modeled using exclusively molecular dynamics. Recent simulations by M. Jaraiz [14] have shown that a good approach for the simulation of ion implantation and annealing at energies on the order of tens of keV, consists on the coupling between binary collision approximation models, like MARLOWE, and Monte Carlo simulations. Following that approach, we use Monte Carlo simulations to study the annealing of defects at high temperatures, and extend the simulation time and scale.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Clusters larger than 5 have binding energies fitted to a function of the form: Ebv(N) = 3.6-4.9(n2'3 -(n-1)2'3)eV and Eb1(n)=2.5-2. 17(n'2-(n-1)1'2)eV, for V and I of size H respectively, See reference [14] for a description of the program.…”
Section: Modeling Of Defect Diffusion: Monte Cnrlo Simulationsmentioning
confidence: 99%